Exploring the Interplay between Young Consumers and the Mobile Location-based Advertising - Zhu, Xun (2018)
In the past few years, as the dramatic development of the functions and capabilities of mobile phones and the diversification of advertising, a relatively new form of advertising – mobile location-based advertising (mobile LBA), which employs the latest geographical location-based technology, is increasingly being utilised by marketers. Although many academics are paying more and more attention to mobile LBA, most of them have mainly focused on the relationship between general consumers and mobile LBA. Little research has been undertaken from young consumers’ perspective Therefore, the aim of this study is to address the gap in previous literature.